PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION PADA SISWA KELAS VII SMP NEGERI 15 BULUKUMBA - Hari Aningrawati Bahri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2016)
This research is Classroom Action Research which aim to increase student’s learning result. The research’s subject is students of VII SMPN 15 Bulukumba year 2011/2012 with the student amount 33 people. The data collect by using observation and result of mathematics test in the first cycle and second cycle and qualitative data is student observation result. The result of the research point out with: 1) Student activity and student response in Cooperative Teaching Type Group Investigation is increased. 2) Cooperative Teaching Type Group Investigation can improve learning mathematics at class VII SMPN 15 Bulukumba 3) the result of learning mathematic at cycle one with average score 56,72 of score ideals 100 with standard deviation 18,00 in low categorize increased in cycle two with average score 75,36 of score ideals 100 and standard deviation 14,65 in high categorize.